Advancing Science Through Diversity and Inclusion in the Editorial Process: A Case Study. (30th August 2019) - Crook, C; Rivera Mindt, M; Hilsabeck, R; Olsen, J; Savin, M; Suchy, Y
Abstract: Objective: In the U.S., women and culturally/linguistically diverse persons are underrepresented in research and editorial boards. This case study details how one journal, The Clinical Neuropsychologist (TCN), created and implemented a strategic plan to advance diversity and inclusion in its editorial board and process. Case Description: In 2015, Dr. Yana Suchy became TCN's first female Editor-in-Chief; and in 2016, she created the Culture and Gender in Neuropsychology Department (CGND). The CGND's Editors are Drs. Rivera Mindt and Hilsabeck, and their mission is to diversify science and empirically-based practice within neuropsychology by (1) increasing representation of editors/reviewers from diverse backgrounds; (2) soliciting articles related to gender/culture; (3) providing resources addressing diversity issues; and (4) demonstrating editorial leadership via editorial content. Diagnostic Impressions and Outcomes: In 2015, only 23% of TCN editors were women and only 2% were from diverse backgrounds. By 2018, representation of these groups increased to 50% and 13%, respectively. Also, in 2018 TCN published its first special issue on gender, numerous articles on culturally diverse populations, and the first guideline for evaluation of transgender persons. An upcoming special issue will focus on normative data for Spanish-speakers. Resources available include a Publication Guidelines Checklist, formal presentations, and informal communications (social media) to educate and engage stakeholders and consultors. These accomplishments were recently highlighted in the inaugural CGND editorial (2018). Discussion: Over the last three years, TCN has taken steps to increase representation of gender- and culturally/linguistically-relevant content, editorial leadership, and professional development; thereby demonstrating that this is a tangible goal. This case study serves as a call to action for other journals to follow suit and further diversify science. References: Rivera Mindt, M.,  Hilsabeck, R. C., Olsen, J. P.,  Savin, M. J., Crook, C. L., & Suchy, Y. Advancing science through diversity and inclusion in the editorial process: A case study. Science Editor, 41 (3), 93-96. Rivera Mindt, M. & Hilsabeck, R. C. (2018)  TCN  culture and gender in Neuropsychology Department: inaugural editorial.  The Clinical Neuropsychologist,  32 (8),  1353-1355,  DOI: 10.1080/13854046.2018.1525110 . Hilsabeck, R. C. (2018) Editorial: Raising awareness about gender bias and disparity in clinical neuropsychology and a call to action.  ClinNeuropsychol, 32, 183–185. https://doi.org/10.1080/13854046.2018.1525110 . Fujii, D. E. M. (2018) Developing a cultural context for conducting a neuropsychological evaluation with a culturally diverse client: The ECLECTIC framework.  The Clinical Neuropsychologist,  32 (8),  1356-1392,  DOI: 10.1080/13854046.2018.1435826 . Trittschuh, E. H., Parmenter, B. A., Clausell, E. R., Mariano, M. J. & Reger, M. A. (2018) Conducting neuropsychological assessment with transgender individuals.  The Clinical Neuropsychologist,  32 (8),  1393-1410,  DOI: 10.1080/13854046.2018.1440632 . Nielsen, T. R.,  Segers, K.,  Vanderaspoilden, V.,  Bekkhus-Wetterberg, P.,  Minthon, L.,  Pissiota, A.,  Bjørkløf, G. H.,  Beinhoff, U.,  Tsolaki, M.,  Gkioka, M., & Waldemar G. (2018) Performance of middle-aged and elderly European minority and majority populations on a Cross-Cultural Neuropsychological Test Battery (CNTB).  The Clinical Neuropsychologist,  32 (8), 1411-1430,  DOI: 10.1080/13854046.2018.1430256 . Suhr J. A., Ready R., Rosen W. G.,  Hilsabeck, R. C., & Ploetz, D. M. The changing face of neuropsychology: gender disparities and strategies for addressing them. CE workshop presented at the 37th annual conference of the National Academy of Neuropsychology, Boston, MA, 2017. Hilsabeck, R. C., Sweet J., Forrest B., Sachs B., & Kubu, C. Gender and the profession of neuropsychology: where we've been and where we need to go. CE workshop presented at the 15th Annual Conference of the American Academy of Clinical Neuropsychology, Boston, MA, 2017. Rivera Mindt, M. 2018. The Clinical Neuropsychologist: increasing diversity & inclusion. Council of Science Editors,  TechnicaEditorial Services Webinar: The Peer Review Ecosystem: Where Does Diversity & Inclusion Fit In? [accessed 2018 Oct 9]. https://www.youtube.com/watch?v=7cixedlVR0o&feature=youtu.be .